Impact of comorbid obsessive-compulsive disorder on suicidality in patients with bipolar disorder. (August 2020) - Di Salvo, Gabriele; Pessina, Enrico; Aragno, Elena; Martini, Azzurra; Albert, Umberto; Maina, Giuseppe; Rosso, Gianluca
Highlights: Obsessive-Compulsive Disorder (OCD) is a common comorbid condition in patients with Bipolar Disorder. OCD comorbidity is associated with higher severity of Bipolar Disorder. OCD comorbidity is not associated with an increased risk of suicide in Bipolar Disorder. OCD comorbidity is a risk factor for violent suicide in patients with Bipolar Disorder. Abstract: This study evaluated the impact of comorbid OCD on suicide attempt risk and suicide methods in 990 patients with main diagnosis of BD. Two hundred and one patients (20.3%) had lifetime comorbid OCD. No significant differences were found comparing rates of lifetime suicide attempts between patients with or without comorbid OCD (30.3% vs 24.6%). In the subgroup of patients with concomitant OCD more subjects performed suicide attempts with violent methods (48.3% vs 28.7%). Therefore, our results suggest a correlation between comorbid OCD and violent suicide attempts. This finding is worthy of interest and deserves to be explored by further studies.